Bacteroides fragilis requires the ferrous‐iron transporter FeoAB and the CobN‐like proteins BtuS1 and BtuS2 for assimilation of iron released from heme. Issue 4 (21st June 2018) - Rocha, Edson R.; Bergonia, Hector A.; Gerdes, Svetlana; Jeffrey Smith, Charles
Abstract: The intestinal commensal and opportunistic anaerobic pathogen Bacteroides fragilis has an essential requirement for both heme and free iron to support growth in extraintestinal infections. In the absence of free iron, B. fragilis can utilize heme as the sole source of iron. However, the mechanisms to remove iron from heme are not completely understood. In this study, we show that the inner membrane ferrous iron transporter ∆feoAB mutant strain is no longer able to grow with heme as the sole source of iron. Genetic complementation with the feoAB gene operon completely restored growth. Our data indicate that iron is removed from heme in the periplasmic space, and the released iron is transported by the FeoAB system. Interestingly, when B. fragilis utilizes iron from heme, it releases heme‐derived porphyrins by a dechelatase activity which is upregulated under low iron conditions. This is supported by the findings showing that formation of heme‐derived porphyrins in the ∆feoAB mutant and the parent strain increased 30‐fold and fivefold (respectively) under low iron conditions compared to iron replete conditions. Moreover, the btuS1 btuS2 double‐mutant strain (lacking the predicted periplasmic, membrane anchored CobN‐like proteins) also showed growth defect with heme as the sole source of iron, suggesting that BtuS1 and BtuS2 are involved in heme‐iron assimilation. Though the dechelatase mechanism remains uncharacterized, assays performed in bacterial crude extracts show that BtuS1 and BtuS2 affect the regulation of the dechelatase‐specific activities in an iron‐dependent manner. These findings suggest that the mechanism to extract iron from heme in Bacteroides requires a group of proteins, which spans the periplasmic space to make iron available for cellular functions. Abstract : Bacteroides fragilis removes iron from heme and releases free protoporphyrin IX in the periplasmic space. Transport of heme derived iron requires the presence of the membrane ferrous iron transporter FeoAB and the CobN‐like chelatases BtuS1 and BtuS2.